Faktor Pencetus Gejala dan Perilaku Pencegahan Systemic Lupus Erythematosus - Ni Putu Wulan Purnama Sari (Jurnal Ners, 2016)
Introduction: Systemic Lupus Erythematosus (lupus) and its unpredictable flares have lowering the patients’ quality of life significantly. Precipitating factors’ exposures need to be reduced by doing preventive behaviors to reduce the frequency of lupus flare. This study aimed to analyze the correlation between precipitating factors and preventive behavior in lupus patients. Method: This is a cros-sectional study. Population was all lupus patients doing regular check-up in Rheumatology Unit of Dr. Soetomo Public Hospital, Surabaya. Sample was lupus patients who did regular check-up in the period of October-December 2014 and matched to sample’s criteria. Sample size was 36 enrolled by means of total sampling. Independent variabel: precipitating factors of lupus flare; dependent variable: knowledge of lupus, attitude (self-efficacy) and preventive action towards exposures. Instruments used were questionnaire of lupus precipitating factors and ODAPUSHEBI (part 1,2,3). Data analysis used Spearman Rho correlation with α<0.05. Result: Most respondents are late adulthood, get married, high school graduates and actively working. The majority had lupus for 1-2 years. Precipitating factors were mostly physical stres (66.7%). Symptom of lupus that most often relapse was joint pain. Knowledge of lupus in all respondents was high, as for attitude mostly were high and most respondents doing optimal preventive action. There was no correlation between the precipitating factors of lupus flare with lupus knowledge (p=0.342) and attitude (p=0.651). There was a weak but significant correlation between the precipitating factors with preventive action (r = 0.360; p=0.031). Discussion: Precipitating factors of lupus flare vary among patients so that preventive actions taken adjust to the type of exposure. The preventive action taken optimally could minimize the recurrence of lupus flare. There is a correlation between the precipitating factors of flare with preventive action in lupus patients.